Paguyuban Sebagai Sarana Keteraturan PKL (Pedagang Kaki Lima) Di Kawasan Alun-Alun Jember - Elegi Nur Aisah; Mila Mufira; Muhamad Helmi Wakhit Yansyah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Street Vendors is one of the informal sector jobs that many people enjoy. However, there are many urban problems caused by the proliferation of street vendors like this. The increasing number of traders has made city planning increasingly chaotic and out of control. Apart from that, conflicts between traders cannot be avoided. This research aims to describe how the chaos that occurs due to the large number of street vendors selling can be overcome by the presence of an association that regulates and manages their activities. Paguyuban exists as a local manager who can create order. Researchers try to analyze this phenomenon by using the conflict theory developed by Ralf Dahrendof.This research uses a qualitative approach which is deemed suitable to describe and explore the above phenomena. Data collection techniques in this research used interview techniques accompanied by field observations.